Protecting Indian health workforce during the COVID-19 pandemic - Behera, Deepanjali (J Family Med Prim Care, 2020)
Rapidly growing rate of infection among health workers during the current COVID-19 pandemic, is posing a serious challenge to global health systems. Lately, India is also witnessing an intensifying COVID-19 disease burden and its impact on health workers. This paper aims to discuss the challenges to health worker protection in India and the possible ways forward. Given the inadequate and unequally distributed healthcare workforce, it is highly essential for the country to strategize prompt measures for ensuring occupational health and safety of its health workers. Information for this paper were gathered by searching PubMed and Google Scholar databases using “COVID-19”, “Infection Control”, “Health worker”, “India” as search keywords in different combinations. In addition, websites of Government of India, relevant UN agencies and leading news agencies were also searched manually for related reports and publications. India must take timely measures in rapid manufacturing and procurement of essential personal protective equipment (PPE) to ensure adequate stockpiling to meet the rising demands. Comprehensive and repeated training with sharply focussed content including usage of PPE kits as well as active surveillance of adherence to recommended protocol are critical in protecting health workers especially the primary care physicians and frontline health staff from the deadly COVID-19 infection. The provision of psychological and financial support for health workers and their families is absolutely critical in building trust and dedicated work efforts by the health workforce for a continuous fight against the deadly disease.